Model Rekrutmen Politik Calon Anggota Legislatif oleh Partai Politik di Kabupaten Sidoarjo - Ahmad Riyadh U.B.; Hendra Sukmana (Universitas Muhammadiyah Sidoarjo, 2015)
The aim of this research was to discuss the model of recruiting candidates for legislative is conducted by political parties in Sidoarjo Regency. This research used descriptive qualitative. This research was conducted at the Governing Council of Political Parties in Sidoarjo Regency. Informants of this study were leaders of political parties in Sidoarjo, legislative candidates from political parties in Sidoarjo. The results showed that the model of recruiting candidates for legislative in accordance with collaboration models included models of Barber, Snowiss, Rush & Althoff et al. This can be seen from some of the steps in the recruitment socialization of registration, selection, after that determination of legislative candidate by a team of Election Campaign Boar (Bappilu) political party in the Sidoarjo Regency and the serial number in accordance with the criteria of the political party chairman and Election Campaign Boar (Bappilu). Furthermore, it is registered with the General Election Commission (KPU) Sidoarjo regency set to be candidates for Legislative (candidates) remain with serial numbers.